Genetic Diversity of the Cameroon Indigenous Chicken Ecotypes - Keambou , T.C.; Hako, B.A.; Ommeh, S.; Bembide, C.; Ngono, E.P.; Manjeli, Y.; Wamonje, F.; Nzuki; Wanjala, B.; Wamalwa, M.; Cho, C.Y.; Skilton, R.A.; et al. (International Journal of Poultry Science, 2014)
Cameroon has a wide range of agro-ecological zones, having indigenous chicken populations which are thought to be adapted and diversified. Genetic diversity of the Cameroon chicken populations from agro-ecological zones I, II, III and IV was assessed using 25 microsatellite markers. A total of 314 chickens were genotyped, revealing 226 distinct alleles and 24 private alleles (10.62%). The mean polymorphic information content was 0.57. The average observed, expected and unbiased frequencies of heterozygote were 0.60, 0.62 and 0.65 respectively, with the mean Shannon index of 1.21. The global inbreeding coefficient among population was 0.13. Inbreeding coefficient varied significantly with 4.27% variation observed among ecotypes. Within ecotypes the highest diversity was observed in the Bafang-Bakou population having 7.92±4.22 alleles per locus, 168.80±4.73 gene copies, 9 private alleles and 0.68±0.02 expected heterozigosity. However the same region displayed the highest inbreeding coefficient (0.13). In all the populations, 67% of the loci did not deviate significantly from the Hardy-Weinberg. The neighbor-joining tree, UPGMA cladogram as well as the Evanno’s population structure parameters revealed existence of 3 clusters in Cameroon chicken populations. The current study confirmed usefulness of microsatellites for studying genetic variation of the Cameroonian indigenous chicken. They demonstrate information on genetic variability of Cameroon local chicken populations, offer steps towards rational decision making prior to genetic improvement and conservation programs, without compromising the existence of each unique genotype.